Factores determinantes del rendimiento en nadadores velocistas: influencia de variables biomecánicas y fisiológicas - Ruiz-Navarro, J. J. (Universidad de Granada, 2023)
Competitive swimming pool events can be split-up in the start, the clean swimming, the turn(s), and the finish phases for in-depth analysis. The contribution of each one of these components is crucial in sprint swimming, since a fraction of a percent difference in performance determines whether a swimmer wins or loses a race. Therefore, the main purpose of this thesis was to increase the understanding of the biomechanical and physiological variables that influence sprint swimming performance. First, in order to investigate the relationship between tethered forces in a flume and sprint swimming performance, 16 male swimmers performed four 30 s tethered swimming tests in a flume at 0, 0.926, 1.124, and 1.389 m·s-1 water flow speeds and 25, 50, and 100 m front crawl trials. Subsequently, to provide a comprehensive approach between two anaerobic tests, muscle strength, and swimming performance, 14 males and 9 females performed an anaerobic critical velocity test, two 30 s tethered swimming tests in a flume at 0, and 1.124 m·s-1 water flow speeds, five pull-ups and countermovement jumps, and 50 m front crawl. Then, physiological and biomechanical variables were evaluated in 13 males and 8 females before and after a five-weeks off-season period to quantify the effects of detraining on 50 m front crawl. Furthermore, a systematic review was developed to provide an overview of the determinants of undulatory underwater swimming (UUS). Lastly, eight male and six female swimmers performed three countermovement jumps and three maximal UUS trials before and after a five-weeks training period. Swimmers were divided into two different UUS training groups (in-water only vs. in-water combined with conical exercises on land) to analyze the impact of skillspecific training and strength training on UUS performance. The results of the present doctoral thesis showed that tethered swimming variables were correlated with sprint swimming performance. These correlations were stronger as the water flow speed increased. The anaerobic critical velocity was positively correlated with tethered swimming in both conditions and both tests were associated with dry-landbased variables and 50 m swimming performance. The five-weeks training cessation evoked a 50 m performance impairment in both sexes. After the five-weeks, it was observed lower stroke rate and clean swimming speed, higher heart rate, anaerobic metabolic power deterioration (only in males), lower in-water force at zero speed (only in males), and upper and lower body strength impairments in males and females, respectively. The systematic search included a total of 15 articles, which provided a substantial body of research on kicking frequency, vertical toe and body wave velocity, angular velocity of the joints, distance per kick, joint amplitudes and mobility, and body position in UUS performance. The five-weeks training protocol evoked UUS improvements in the combined group (in-water and dry-land exercises), whereas no changes were elicited in the in-water only training group. Collectively, the results of this doctoral thesis suggest that the propulsive force depends on the swimmer`s muscular strength production and the swimmers` ability to effectively apply that force in the water, both of which should be taken into consideration when training and monitoring. Tethered swimming and the anaerobic critical velocity might be used as interchangeable tools for evaluating anaerobic performance. Coaches should find alternatives to minimize the detraining effects prompted during the offseason. Moreover, this doctoral thesis suggests that caudal momentum transfer as well as vertical toe velocity should be maximized to improve UUS performance, taking into account individual characteristics. Furthermore, specific lower limbs strength exercises in conjunction with in-water training should be performed to improve UUS performance.